Vapor pressure measurements over supercooled water in the temperature range from −101 °C to +10−2 °C. (February 2017) - Beltramino, G.; Rosso, L.; Smorgon, D.; Fernicola, V.
Graphical abstract: Highlights: New accurate vapor pressure measurements over supercooled water from 261 K to 273 K. Relative uncertainty varies from 0.039% to 0.085%. Favorable comparison with respect to literature data and saturation water vapor pressure formulations. Abstract: An accurate measurement of saturation vapor pressure of supercooled water is a strong challenge in metrology, mainly due to difficulties concerning keeping water at a liquid state at temperatures well below the melting point; thus few experimental data covering limited temperature ranges (down to about 253 K) are reported in literature. For this reason, an investigation of the water vapor – supercooled water equilibrium along the saturation line is carried out at Istituto Nazionale di Ricerca Metrologica (INRIM). Measurements cover the temperature range from 261.26 K to 273.25 K, corresponding to a saturation vapor pressure from about 244 Pa to 611 Pa. The experimental apparatus includes a borosilicate glass sample cell, kept in a liquid bath at a constant temperature with millikelvin stability and connected to a manifold where the pressure is measured using a capacitive diaphragm pressure gauge. In this work, the water sample preparation, the measuring method and measurement corrections are reported; moreover, a comparison between experimental and literature data is conducted along with the most used vapor pressure formulations. Measurement results are discussed and uncertainty sources estimated. The resulting expanded relative uncertainty ( k  = 2) varies from 0.085% at 261.26 K to 0.039% at 273.25 K.